Antecedents of student satisfaction in higher education: the role of identification - Wilkins, S.; Butt, Mohsin; Kratochvil, Daniel; Stephens Balakrishnan, Melodena (2014)
The concept of student satisfaction has become a key indicator of service quality used by students, parents, university managers and the media as the higher education market becomes increasingly competitive. The purpose of this research is to investigate the antecedents of student satisfaction and in particular the role that different types of identification might have. The sample comprised 437 students enrolled in undergraduate and postgraduate programmes at two universities, one in the United Kingdom (UK) and one in the United Arab Emirates (UAE). A causal model was developed and tested using structural equation modelling. It was found that organisational identification appears to be a stronger predictor of student satisfaction than social identification. Also, student achievement acts as a mediator in the relationship between social identification and student satisfaction. The implications for higher education institutions are discussed.